Reform of Human Resources Management Through Merit System at West Java Regional Personnel Agency - Sampe, Valentin Laura; Rasdiyanti, Andi; Herdayani Darsim, Sitti Khadijah (KnE Social Sciences, 2022)
West Java was ranked first in a merit system evaluation by the State Civil Apparatus Commission in 2020. West Java also won the Meritrocation Award 2020 with a score of 375, up 198 points from the previous year. The purpose of this research was to find out how the Province of West Java was able to reform its human resource management system by implementing a merit-based system. A descriptive qualitative approach was used. The primary data for this study were collected through interviews with career officials from West Java Province’s Regional Personnel Agency (BKD). Documents and personal observations were used to gather secondary data. According to the findings, the Province of West Java has done an excellent job of reforming the human resource management system by implementing a merit system through the BKD. The use of all-encompassing and integrated information and technology was one of two key factors in the successful implementation of meritocracy, the second of which was the importance of high officials. Keywords: merit system, public civil servant, West Java Regional Personnel Agency